COMMENTS ON UTKIR HASHIMOV'S STORY "AFFAIRS OF THE WORLD" - Farkhodova Shohista Hayotovna; Scientific supervisor: M. Mirsanova (Western European Studies, 2024)
This article talks about the high role of mothers in human life, attention to mothers, love of mothers for their children. Also, Utkir Hashimov's book "Works of the World" talks about issues such as how the mother is embodied, and the statement of thoughts from excerpts from short stories.
Keywords: Mother; creator; story; novel